PENGARUH SARANA DAN PRASARANA TERHADAP PRODUKTIVITAS KERJA UKM DI KOTA MAGELANG - Harsono Harsono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
It is the research of effect of local Government facilitation to work the Cluster work’s productivity in Magelang city the innovative city of snacks cluster in Magelang city. Research problem: How is the state quality of the infrastructure. How big is the influence of the independent variables (Promotion, Training and tool Assistance) to the dependent variable of work productivity. The purpose of the research : To pigure out the picture og SME’s infrastructures quality and the level of the influence of independent variables to dependent variable. Expected significance: The results of the research will be used as input of the decision making. The location of the research Magelang city. The method of the research : The population is 240 KUB and sample: The is 40 persons. To determine the samples, simple random sampling method is used. Data analyzing method is inferential statistics model. Results: Conclusions for f count > f table (16.078> 2.87) so Ho is rejected, H altf. Is acceptable. It means there are significant ibfluenses of promotion, training and assistance and tool asintence altogether to the productivity of work. The development of human resources (HR). The improvement of human resources quality is done through, seminar and workshop, on the job training, and cooperative effort.